Catalisadores de níquel-zircônia suportados em nanotubos de carbono para reação de metanação de CO₂ - Oliveira, João Pedro Bueno de (2025)
The conversion of CO2 into methane via the methanation reaction has attracted significant interest due to its potential to mitigate greenhouse gas emissions and contribute to the production of sustainable fuels. In this context, nickel-based (Ni) catalysts stand out due to their high activity, selectivity, and favorable cost-effectiveness. However, the stability and resistance to sintering of Ni catalysts remain significant challenges. This study investigates the performance of Ni and Ni-ZrO2 catalysts supported on carbon nanotubes (CNTs) with the aim of optimizing their catalytic properties through the internal impregnation of active species. The impregnation of metals within the CNTs seeks to enhance the dispersion of metallic nanoparticles, reduce sintering, and increase the thermal and chemical stability of the catalysts during the reaction. The catalysts were prepared using the incipient wet impregnation method, employing functionalized CNTs as a support. Structural and textural characterization was performed using various techniques, including X-ray diffraction (XRD), nitrogen physisorption, thermogravimetric analysis (TGA), X-ray fluorescence spectroscopy (XRF), transmission electron microscopy (TEM), and temperature-programmed reduction (TPR-H2). These analyses allowed for the evaluation of morphology, metal dispersion, and the interaction between Ni and ZrO2 within the CNT supports. Catalytic tests were conducted in a quartz tubular reactor coupled to a gas chromatograph, operating at different temperatures (200–400°C) and using a molar H2:CO2 ratio of 4:1. CO2 conversion and methane selectivity were calculated based on carbon balance. Additionally, the stability of the catalysts was assessed through prolonged tests at 350°C for 24 hours. The results indicated that the combination of Ni and ZrO2 within CNTs significantly improves metal dispersion, leading to a larger active surface area and enhancing the efficiency of the methanation reaction. Catalysts prepared by co-impregnation exhibited superior performance in terms of CO2 conversion and CH4 selectivity compared to those prepared by sequential impregnation. The presence of ZrO2 was crucial for maintaining catalytic activity over time. Furthermore, it was observed that the impregnation of Ni after the addition of ZrO2 favored metal interaction, promoting a synergistic effect that enhanced catalyst stability. Based on the obtained data, it can be concluded that the use of CNTs as a support, combined with Ni and ZrO2, represents an efficient approach for developing more stable and effective catalysts for CO2 methanation. Catalysts employing the co-impregnation strategy demonstrated advantages in maintaining metal dispersion and thermal stability, making them a promising alternative for industrial applications focused on CO2 valorization and the production of sustainable synthetic fuels.